Determination of the prevalence and virulence properties of aerobic endospore-forming bacteria isolated from commercial packaged foods in Dhaka city - Syeed, Shabnam (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.